2020
DOI: 10.5588/ijtld.19.0458
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid and verapamil modulatory activity and efflux pump gene expression in Mycobacterium tuberculosis

Abstract: INTRODUCTION: Resistance to first-line anti-tuberculosis drugs is a major concern in the treatment of the disease. New strategies, such as the use of efflux pump inhibitors (EPIs), are being investigated to improve the outcome of the treatment. Verapamil (VP), one such inhibitor, was shown to inhibit several efflux pump (EP) Mycobacterium tuberculosis proteins and demonstrate synergic activity with anti-TB drugs.OBJECTIVE: To evaluate the combinatory effect of isoniazid (INH) and VP in M. tuberculosis.METHODS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…In some previous studies, it was noted that when VP was used in combination with anti-tuberculosis drugs [including first- and second-line drugs ( 11 , 29 , 30 ) as well as some newly developed new drugs ( 31 )], it showed significant effects both in vivo and in vitro . However, in this study, VP did not have a significant effect on INH mono-resistant isolates, which is consistent with the results of previous studies ( 17 ). However, in contrast, other studies ( 12 , 17 ) pointed out that VP reduces the INH MICs for almost all INH-resistant strains.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In some previous studies, it was noted that when VP was used in combination with anti-tuberculosis drugs [including first- and second-line drugs ( 11 , 29 , 30 ) as well as some newly developed new drugs ( 31 )], it showed significant effects both in vivo and in vitro . However, in this study, VP did not have a significant effect on INH mono-resistant isolates, which is consistent with the results of previous studies ( 17 ). However, in contrast, other studies ( 12 , 17 ) pointed out that VP reduces the INH MICs for almost all INH-resistant strains.…”
Section: Discussionsupporting
confidence: 93%
“…However, in this study, VP did not have a significant effect on INH mono-resistant isolates, which is consistent with the results of previous studies ( 17 ). However, in contrast, other studies ( 12 , 17 ) pointed out that VP reduces the INH MICs for almost all INH-resistant strains. Possible explanations for such contradictory results are that the efflux pump genes did not show significant overexpression in the clinical isolates in this study, so that VP did not show significant effect to reverse bacterial resistance.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“… 36 Previous studies showed verapamil, one of the efflux pump inhibitors, could effectively inhibit drug efflux. 37 At the same time, studies have also demonstrated that combining verapamil with isoniazid or rifampicin (RIF) can cause the MIC of isoniazid (INH) or RIF reduction and even reverse the resistance of MTB. 38 About 20 genes in the genus MTB have been identified as related genes encoding efflux pumps, mainly concentrated in MFS, RND, and SMR.…”
Section: Antibiotic Resistance Of Mtbmentioning
confidence: 99%
“…Additionally, LTCC ion channel blockers can alter iron-associated metabolic pathways thereby impeding iron accessibility which lowers intracellular bacterial survival ( 143 ). Furthermore, verapamil acts synergistically with first-line anti-TB drugs- INH ( 152 ), and RIF ( 153 ) in lowering the bacterial burden in cultures, macrophages, and murine models of TB. In another study, antimycobacterial activity of verapamil was confirmed with several TB drugs including bedaquiline (BDQ) and clofazimine (CFZ) and decreased bacterial load was linked with induction of membrane stress responses as a consequence of verapamil induced membrane function disruption ( 154 ).…”
Section: Targeting Host Ion Channelsmentioning
confidence: 99%